Ecological material solutions with use of composites - Damian Jończyk (Acta Scientiarum Polonorum. Architectura)
Due to the global problem related to the excessive amount of waste, measures are also taken in the construction industry to protect the environment and implement recycled waste for the production of building materials. Due to the high popularity of composite materials in construction, a brief overview of modern ecological solutions using recycling was presented. The presented solutions are divided into three groups: the use of recycled aggregates for the production of concrete, the use of recycled aggregates for structures reinforced with geo-synthetics, and the use of recycled plastic for the production of wood-plastic composites (WPCs). The division into these three groups was determined on the basis of the selection of solutions most widely discussed in scientific articles in the field of recycling. The strength of the elements was mainly analyzed. The most widely used and showing the best strength values is the solution based on the use of recycled aggregate. The use of plastic waste is possible, but requires further research.